Exploring Adolescent Resilience During COVID-19 in a South African Township Context - Shannon Enid Wakefield; Linda Theron (National Youth Advocacy and Resilience Journal, 2023)
COVID-19 has permeated news since December 2019 and has impacted all areas of life. Despite widespread coverage of COVID-related risks, there is limited understanding of adolescent resilience in Global South contexts (e.g., Africa) and against the backdrop of COVID-19. We, therefore, conducted a qualitative secondary analysis of 79 documents (i.e., drawings and written explanations) generated by school-attending adolescents in grades eight to ten in Zamdela, South Africa, during 2020 lockdown. Using a multisystemic resilience approach, we explored what these documents revealed as resilience enabling for adolescents in a township context during COVID-19. The thematic findings highlight the importance of personal resources, complemented by relational resources and very occasionally, resources in young people’s physical ecology. These findings reinforce that resilience is more than a set of personal strengths and reminds us that individual capacity for resilience is pertinent when contextual and temporal dynamics such as resource constraints and lockdown conditions prevail.